A Free Society Reader: Principles for the New Millennium - Novak, Michael,; Brailsford, William,; Heesters, Cornelis, (Lexington Books, 2000)
A Free Society Reader rises to the challenge of freedom in the twenty-first century, offering thoughts and insights with significant implications for citizens of today's brand new world. Our era's most prominent figures in the fields of Christianity and liberty speak about Pope John Paul II's vision of a free society, conceptualize Christianity and political economy, debate issues of democracy and the free society, and question the role of culture. Together for the first time in one volume, these preeminent thinkers provide inspiration and insight to scholars, students, and general readers charting the enormous changes the new millennium has seen.